The impact of bariatric and metabolic surgery on cancer development - Lunger, Fabian; Aeschbacher, Pauline; Nett, Philipp C.; Peros, Georgios (Frontiers in Surgery, 2022)
Obesity is one of the most common preventable risk factors for cancer development worldwide. It is responsible for at least 40% of all newly diagnosed cancers, including colon, ovarian, uterine, breast, pancreatic, and esophageal cancers. Although various efforts are being made to curb the increasing incidence of obesity, morbid obesity (BMI >35 kg/m2) has concomitant diseases such as type 2 diabetes mellitus, cardiovascular disease, sleep apnea syndrome, and the fatty liver disease continues to spread in the Western world. Currently, bariatric and metabolic surgery is the most effective treatment strategy for patients suffering from morbid obesity with concomitant diseases who cannot lose weight with a medically supervised diet and exercise program. This review addresses basic studies that have examined the potential cancer-preventive effects of bariatric and metabolic surgery and demonstrate a beneficial effect. Although bariatric and metabolic surgery cannot be routinely recommended as a cancer prevention strategy, considerations in this regard should always play a role in treating and preventing patients with complex diseases.